Ameliorating Effect of Oral Guggulsterone Administration in Imiquimod-Induced Psoriasis in Mice - A. Khaleel, Raghad; H. Zalzala, Munaf (Iraqi Journal of Pharmaceutical Sciences, 2018)
Psoriasis is a common chronic skin condition characterized by infiltration of inflammatory cells into the epidermis and altered keratinocyte differentiation.In this work, psoriasis was induced by an imiquimod 5% cream, an immune response modifier that can induce psoriasis-like skin inflammation when applied topically in mice. Guggulsterone prepared as a suspension and has been orally given to mice before imiquimod application. The results of the current study showed that guggulsterone suspension can significantly reduce psoriasis area and severity index in (guggul suspension+imiquimod group as compared with both control group and (vehicle suspension+imiquimod ) group.